THUNDERBIRDS. (From Abba to Zoom: A Pop Culture Encyclopedia of the Late 20th Century, 2005)
Information about "Thunderbirds," a childhood science-fiction television show, is presented. The show was another marionette adventure created by Gerry Anderson which was originally aired on television from 1965-1966. It is reported that several spin-offs, feature films and a rock band got inspiration from the television program.